2023
DOI: 10.3390/en16052256
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salty Environments on the Degradation Behavior and Mechanical Properties of Nafion Membranes

Abstract: The application of proton-exchange membrane fuel cells (PEMFCs) in maritime transportation is currently in the spotlight due to stringent emissions regulations and the establishment of a carbon trading system. However, salt in the marine environment can accelerate the degradation of proton-exchange membranes (PEM), which are the core component of PEMFCs. In this study, the effect of the NaCl concentration and temperature on the degradation of Nafion, the benchmark PEMFC membrane, was analyzed ex situ by accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…We found that this mass loss was not observed in similar experiments using pure water with any one of the non-irradiated samples. Some studies showed that the presence of Na + affects the intramembrane transport properties [ 26 , 27 ]. Madhav et al [ 26 ] used accelerated degradation via Fenton´s test to examine the influence of Na + presence in membrane degradation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that this mass loss was not observed in similar experiments using pure water with any one of the non-irradiated samples. Some studies showed that the presence of Na + affects the intramembrane transport properties [ 26 , 27 ]. Madhav et al [ 26 ] used accelerated degradation via Fenton´s test to examine the influence of Na + presence in membrane degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed that the presence of Na + affects the intramembrane transport properties [ 26 , 27 ]. Madhav et al [ 26 ] used accelerated degradation via Fenton´s test to examine the influence of Na + presence in membrane degradation. They observed that the presence of NaCl accelerated the degradation of Nafion membranes in salty environments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to ensure better forecast accuracy of the fuel cell's lifetime and analyze its probable degradation mechanism, the accelerated stress tests (ASTs) have been implemented by many researchers in experimental studies with regard to the contamination in hydrogen and air [4,5], start-up at subzero temperature [6][7][8][9] and dynamic response under driving cycles [10]. For the on-board fuel cells in vehicles, the performance degradation consists of membrane degradation, Pt/C catalyst degradation and gas diffusion layer degradation [11][12][13][14][15][16][17][18][19]. More specifically, the typical membrane degradation includes cracks, punctures and pinholes, resulting from a harsh operating environment accompanied by improper temperature, relative humidity and mechanical conditions.…”
Section: Introductionmentioning
confidence: 99%